O ensino do relacionamento interpessoal enfermeiro – paciente: avaliação dos alunos - Furegato, Antonia Regina Ferreira (2006)
Abstract: The authors aimed at evaluating the teaching of the subject Nurse-Patient Interpersonal Relationships to graduate students. The instruments for data collection made it possible to learn about: 1) the readings done; 2) the opinions of a group of nineteen students on the objectives, distribution of activities, recommended texts, practical activities and teaching methodology; 3) the students' feelings in relation to teaching/learning, the dynamics of this experience and their profession. Results 1) the students read less than what was expected; 2) they need more time to discuss about practical experiences; 3) they evaluated their professional development; 4) they experienced new positions when facing patients; 5) they agreed that a nurse's role can be therapeutic. Key words: Interpersonal relationship, therapeutic interaction, teaching, nursing, evaluation